Plasma S1P (Sphingosine-1-Phosphate) Links to Hypertension and Biomarkers of Inflammation and Cardiovascular Disease: Findings From a Translational Investigation. Issue 1 (17th May 2021) - Jujic, Amra; Matthes, Frank; Vanherle, Lotte; Petzka, Henning; Orho-Melander, Marju; Nilsson, Peter M.; Magnusson, Martin; Meissner, Anja
Abstract : Supplemental Digital Content is available in the text. Abstract : S1P (Sphingosine-1-phosphate) is an important regulator of immune cell trafficking and vascular dysfunction contributing to the development and progression of overt hypertension. Although targeting S1P signaling revealed therapeutic potential in different experimental hypertension studies, validations of S1P-blood pressure (BP) associations in humans are lacking. In a translational approach, we explored the associations between plasma S1P and BP in a family based study cohort (MOS [Malmö Offspring Study]; N=1046) and in a longitudinally conducted murine hypertension cohort. In MOS, linear multivariate regression analyses showed that plasma S1P associates with increased systolic BP (β=1.06, P =0.015). Study subjects with systolic BP ≥140 mm Hg presented with significantly higher S1P plasma concentrations compared with subjects with BP <120 mm Hg independent of age and sex. The S1P-BP association was validated in a murine model where plasma S1P increased with systolic BP ( r =0.7018, R 2 =0.4925; P <0.0001). In a subsample of MOS (N=444), proteomic profiling for markers of inflammation, metabolism, and cardiovascular disease using Proximity Extension Assays revealed multiple significant S1P associations, some of them with marked sex-specificity. In vitro and ex vivo validation of identified S1P associations disclosed augmented expression of different vascular dysfunction and inflammation markers in response to S1P. Our translational findings show a link between plasma S1P and systolic BP as well as several inflammation and cardiovascular disease markers and suggest S1P's biomarker potential. This encourages further studies to investigate its predictive capacity for hypertensive disease or the therapeutic potential of its signaling axis.